Penyuluhan Cara Mengatasi Gangguan Kecemasan Sebelum Dan Sesudah Bertanding Pada Atlet Putra Bolavoli - Rosi Rosalina (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Community Service Counseling on Strategies to Overcome Anxiety Disorders in Athletes Before and After Competition aims to enhance athletes’ knowledge, understanding, and insight so that these strategies can be applied when they are experiencing anxiety before and after competitions. Anxiety is one of the psychological disorders that significantly affects athletic performance during competition. When an athlete’s performance declines, it also impacts the level of achievement attained. The partners in this community service program are male volleyball athletes aged 17–19 years from Probolinggo Regency. The approach method offered to address the problem includes direct discussions with athletes and coaches, as well as providing knowledge on strategies to manage anxiety levels ranging from mild and moderate to severe anxiety. Data collection techniques were carried out using questionnaires to assess athletes’ knowledge regarding anxiety levels. The problem-solving approach involves direct discussions with the community, designing and preparing the necessary tools and materials, and conducting counseling sessions on how to overcome anxiety disorders in athletes, particularly before and after competitions. Through this counseling program, it is expected that athletes will be able to effectively manage and control their own anxiety before and after competitions, as well as understand how to analyze their own anxiety levels and those of their fellow athletes.